Penerapan Aljabar Linear dan Matriks dalam Pengembangan Game Digital - Ahmad Handika Akbar (PT Pustaka Cendekia Group, 2024)
The rapid development of the digital game industry demands a strong integration between computer science and mathematics, particularly in the field of linear algebra. Linear and matrix algebra are the backbone of computer graphics systems, animation, physics simulations, and even artificial intelligence (AI) in games. This paper discusses the basic principles of linear algebra and their application in game development, such as object transformations, camera setup, and motion simulation. This study aims to provide conceptual and practical understanding for game developers and encourage the use of mathematical approaches in the design and development process.